Comprehensive study of nine novel cases of TFEB‐amplified renal cell carcinoma: an aggressive tumour with frequent PDL1 expression. Issue 2 (13th June 2022) - Kammerer‐Jacquet, Solène‐Florence; Gandon, Camille; Dugay, Frederic; Laguerre, Brigitte; Peyronnet, Benoit; Mathieu, Romain; Verhoest, Grégory; Bensalah, Karim; Leroy, Xavier; Aubert, Sebastien; Vermaut, Catherine; Escande, Fabienne; et al.
Abstract : Aims: First described in 2014, renal cell carcinoma (RCC) with TFEB amplification (6p21) is a rare molecular subgroup whose diagnosis is challenging. The prognosis and therapeutic implications remain unclear. Methods: We report here the clinical, histological, immunohistochemical, and genetic features of nine novel cases. The pathological and immunohistochemical features were centrally reviewed by expert uropathologists. Fluorescence in situ hybridisation (FISH) confirmed the diagnosis and comparative genomic hybridisation (CGH) was performed to determine quantitative genomic alterations. We also performed an exhaustive review of the literature and compiled our data. Results: TFEB ‐amplified RCC were locally advanced, with initial lymph node involvement in one case and liver metastasis in another case. They were high‐grade eosinophilic tumours with papillary/pseudopapillary architecture, frequent positivity for melanocytic markers, and frequent PDL1 expression. FISH demonstrated high‐level TFEB amplification in six cases. One case showed concomitant TFEB translocation. CGH analysis identified complex alterations with frequent losses of 1p, 2q, 3p, 6p, and frequent 6p and 8q gains. VEGFA coamplification was identified in all cases with a lower level than TFEB. The prognosis was poor, with five patients having lymph node or distant metastases. Conclusion: TFEB ‐amplified RCC is a rare molecular subgroup with variable morphology whose diagnosis is confirmed by FISH analysis. The complex alterations identified by CGH are consistent with an aggressive clinical behaviour. The coamplification of VEGFA and the expression of PDL1 could suggest a potential benefit from antiangiogenics and targeted immunotherapy in combination for these aggressive tumours. Abstract :